Evaluation of Cognitive Function in Relation to Progression of Parkinson Disease. (July 2020) - Yamawaki, Rie; Nankaku, Manabu; Kusano, Yusuke; Tajima, Ayumi; Ikeguchi, Ryosuke; Matsuda, Shuichi
Abstract: Objective: Cognitive impairments are among the nonmotor symptoms in patients with Parkinson disease. Understanding the cognitive impairments in patients with Parkinson disease may be critical for developing effective rehabilitation interventions. The aims of this study were to assess cognitive function in patients with Parkinson disease using the Wechsler Adult Intelligence Scale Third Edition, and the Wechsler Memory Scale Revised and to investigate how cognitive impairments relate to progression of disease in patients with Parkinson disease according to the Hoehn and Yahr stages. Design: Seventy-eight patients with Parkinson disease participated in the present study. Our study consisted of patients in the following Hoehn and Yahr groups: 1 (no disability, n = 11), 2 (mild, n = 34), 3 (moderate, n = 26), and 4 and 5 (severe, n = 7). Cognitive function was assessed using the Wechsler Adult Intelligence Scale Third Edition, and the Wechsler Memory Scale Revised. Results: The verbal memory was significantly higher in group 1 (106.4 ± 12.0) than in the other groups (2: 90.5 ± 14.0, 3: 89.9 ± 16.9, 4 and 5: 89.6 ± 11.4). Visual memory and delayed recall were similar to the results seen with verbal memory; however, the differences between groups were not statistically significant. The full-scale IQ was not significantly different (1: 107.3 ± 8.1, 2: 96.9 ± 18.2, 3: 96.7 ± 14.8, 4 and 5: 91.7 ± 9.5). Conclusions: These results suggest that a comprehensive assessment focused on memory impairments is important for applying the appropriate interventions in patients with early-stage Parkinson disease. Abstract : Supplemental digital content is available in the text.